Nilai-Nilai Pendidikan Agama Islam Dalam Membangun Karakter Islami Siswa Melalui Kegiatan Gebyar Ramadhan Di SMP Negeri 1 Muara Badak - Muhammad Jafar (Tasamuh: Jurnal Studi Islam, 2025)
The purpose of this study is to analyze in depth the implementation of Islamic Religious Education (PAI) values and their contribution to building Islamic character in students through the Gebyar Ramadhan (Ramadan Celebration) activities at SMP Negeri 1 Muara Badak. This study also aims to identify the supporting and inhibiting factors in the program. The research uses a qualitative approach with a case study method, located at SMP Negeri 1 Muara Badak, with data collection through observation, interviews, and documentation. The results of the study show three main findings. First, the implementation of PAI values is effectively integrated through the habit of collective worship (daily congregational prayers) which fosters discipline and obedience, as well as sharing programs (charity and social service) which instill social awareness and responsibility. Second, the mechanism of contribution of this program is through the acceleration of value internalization by utilizing the spiritual momentum of Ramadan and creating intensive collective practice-based learning (such as the Daily Practice Journal), which transforms moral knowing into moral action. Third, the main supporting factors are the commitment of school leaders and the synergy of teachers across subjects as role models, while significant inhibiting factors include suboptimal family support in monitoring follow-up at home and limited worship facilities. Overall, Gebyar Ramadhan proved to be an effective character laboratory.